5th International Conference EnRe-Energy&Responsibility: Book of Extended Abstracts (University of Maribor Press, 2022)
The tendency to improve energy devices, the impact of environmental factors and the development of new technologies for the exploitation of sustainable resources contribute to the fact that we have witnessed intensive energy development in the last decade. The two most important Slovenian energy pools, located in Velenje and Krško, are at the turning point of renovation, and are facing major challenges in the design and planning of modern energy devices. The current generation faces a great ethical responsibility to leave their descendants a world with as little human impact on the environment as possible. Therefore, communication between experts and researchers, discussion and exchange of different views for the future is of the utmost importance, which is exactly the purpose of the EnRe Conference.